Root hydraulic conductance, gas exchange and leaf water potential in seedlings of Pistacia lentiscus L. and Quercus suber L. grown under different fertilization and light regimes - Hernández, E I; Vilagrosa, A; Luis, V C; Llorca, M; Chirino, E; Vallejo, V R (Environmental and Experimental Botany, 2009)
Differences in morphology, biomass allocations and physiological responses were investigated in seedlings of Mastic tree (Pistacia lentiscus L.) and Cork oak (Quercus suber L.) submitted to contrasting fertilization and light regimes during early growth. These species are two evergreen sclerophyllous Mediterranean species frequently used in Mediterranean reforestation programmes. Fertilization was the treatment that affected most of the morphological and physiological variables evaluated in P. lentiscus and Q. suber seedlings. Leaf area and speciﬁc leaf area (SLA) were affected by shading treatment in both species, showing higher values in seedlings grown under shade. P. lentiscus seedlings showed a high capacity to modify root morphological variables and root hydraulic conductance (KR) with the fertilization treatment. In contrast, Q. suber showed low to moderate root system changes with the treatments applied, although the fertilization level affected biomass allocation (i.e., root to shoot ratio) in both species. Under high water demand, P. lentiscus seedlings with high KR allowed transpiration (E) to increase without increasing the water potential gradient between soil and leaves. In Q. suber, high fertilization induced signiﬁcant increases in photosynthesis (A), as well as a tendency to increase E with signiﬁcantly lower leaf water potential ( L)
Keywords: Drought; fertilization; Gas exchange; light; Root hydraulic conductance

Effects of a deep container on morpho-functional characteristics and root colonization in Quercus suber L. seedlings for reforestation in Mediterranean climate - Chirino, E; Vilagrosa, A; Hernández, E I; Matos, A; Vallejo, V R (Forest Ecology and Management, 2008)
In the last decades, reforestation and afforestation programs are being carried out mainly with containerized seedlings. Container design determines the morphological and physiological characteristics of seedlings. However, container characteristics are often the same for plant species with very different growth strategies. The most commonly used nursery containers are relatively shallow and limit tap root growth; consequently, species relying on the early development of a long tap root to escape drought, such as those of the Quercus genus, might need to be cultivated in deep containers. The aim of this paper was to compare the morphological and physiological characteristics of Quercus suber L. seedlings cultivated in shallow containers (CCS-18, depth 18 cm) with seedlings cultivated in deep containers (CCL-30, depth 30 cm). Both container types used were made of high-density polyethylene, cylindrical in shape, open-bottomed, with a diameter of 5 cm, two kinds of vertical ribs on the inside wall showing a cultivation density of 318 seedlings/m2 . At the end of nursery culture, the seedlings cultivated in the CCL-30 deep container presented a longer tap root, higher shoot and root biomass and higher Dickson Quality Index (DQI). Moreover, the CCL-30 seedlings showed a higher root growth capacity (RGC), they reached deep substrate layers faster and they presented higher root hydraulic conductance. These morpho-functional advantages improved the CCL-30 seedling water status, which was expressed by higher stomatal conductance during an imposed drought period
Keywords: Forest tray; Hydraulic conductance; root system; Stomatal conductance

Organic carbon and nitrogen mineralization under Mediterranean climatic conditions: the effects of incubation depth - Rovira, P; Vallejo, V R (Soil Biology and Biochemistry, 1997)
n a soil profile, temperature and humidity regimes change with depth. Under Mediterra- nean conditions, upper horizons are more affected by water deficits and drying-rewetting cycles than deep horizons. Our aim was to study how carbon and nitrogen mineralization are affected by depth, and special attention is paid to separating the effects of pedoclimate from the effects of other con- straints like amount and quality of organic matter. To this end, mixtures of plant + soil material were exposed by incorporation in the field, at depths of 5, 20 and 40 cm, in nylon mesh bags. Mineralization of C and N was studied for 2 y. For all types of plant material studied (Eucalyptus globulus, Quercus ibex and Pinus halepensis), mineralization of both carbon and nitrogen was lower at 5cm. No differ- ences were between 20 and 40 cm. This result, probably as a result of the higher drying of the upper- most horizons, contrasts with the usual findings on this topic. The amounts of both C and N mineralized were lower than expected, probably because plant materials were finely ground, allowing stabilization in the mineral matrix of soil. With the possible exception of Pinus, depth affected the rate of mineralization, not the relation between C and N. It is concluded that, at least under Mediterranean conditions, the pedoclimate in deep layers is more favourable to microbial activity than in upper layers, in which drought is a strong limiting factor. Reduced oxygen availability in the subsoil layers did not inhibit decomposition and mineralization to the same extent as did desiccation in the surface layer. The higher mineralization of C and N usually found in upper horizons may be attributed to the higher amount and quality of organic matter in these horizons, rather than to pedoclimatic constraints
Keywords: mineralization; organic matter (voyant); Soil depth; water content

Una nueva técnica viverística para la introducción de plantones de DE QUERCUS SPP. EN CLIMA SECO Y SEMIÁRIDO - Vilagrosa, A; SEVA, J P; Valdecantos, a; HERNÁNDEZ, N; CORTINA, J; Bellot, J; Vallejo, V R (II Congreso Forestal Español, 1997)
We present a new technique to improve the establishment of Quercus spp. seedlings in dry and semiarid environments. It is based on the use of pre-germinated acorns transplanted in biodegradable nursery container which are transferred to the field befo re root pruning and upward root growth occurs. In this experiment we also tested the use of tree-shelters.
Keywords: bellotas pregerminadas (voyant); clima mediterráneo; plantones; Quercus spp.; supervivencia

MIGRATION STUDY OF RADIONUCLIDES IN A MEDITERRANEAN FOREST SOIL USING SYNTHETIC AEROSOLS - SAURAS, T; ROCA, M C; Tent, J; Llauradó, M; VIDAL, M; Rauret, G; Vallejo, V R (SCIENCE OF THE TOTAL ENVIRONMENT, 1994)
Radionuclide migration in a Mediterranean forest was studied in field conditions. Fresh Holm oak leaves were exposed to a synthetic aerosol including Cs-134, Sr-85 and Ag-110m, and were incubated in the original Holm oak forest in two types of cylinder: (1) cylinders in which the contaminated litter lies directly on the original F layer; (2) cylinders with an exchange resin bag inserted between the contaminated litter and the underlying F layer. The results for 232 days of incubation showed that Cs-134 presented an initial rapid leaching period, which corresponded to the fraction extracted with water from the initially contaminated leaves. Further Cs-134 release was related to litter decompostiion. Sr-85 migration was studied for only 76 days, and its behaviour appeared to be similar to Cs-134. Both radionuclides migrated within the litter leachates. After 3 months of incubation, around 70% of the initial Cs-134 was transferred to the underlying layers, mainly to the F layer. Cs-134 absorbed into the leaves was released at the same rates as K. The Ag-110m activity lost from the contaminated litter amounted to around 45% in the open cylinders, from which 15-20% was attributed to the effect of soil faunal activity. The field method proposed proved to be useful in describing radionuclide migration in situ and the mechanisms involved.
Keywords: litter; mediterranean forest; RADIONUCLIDE MIGRATION